Harmonization of Pancasila Values with the Principles of Maqasid Al-Syariah in the Framework of the Unitary State of the Republic of Indonesia (NKRI) - Saman Nst, Abdul (Ipso Jure, 2026)
This research aims to comprehensively examine and analyze the harmonization of Pancasila values with the principles of Maqasid Al-Syariah within the framework of the Unitary State of the Republic of Indonesia (NKRI), as a conceptual and practical effort in strengthening national integration in the midst of the reality of pluralistic and religious Indonesian society. The research problem departs from the existence of discursive tensions regarding the relationship between religion and the state, which in some contexts has the potential to give birth to social fragmentation and ideological conflicts. Therefore, an integrative approach is needed that is able to dialogue national values with religious normative values in a constructive, systematic, and sustainable manner. This research uses a qualitative approach with a type of library research that is enriched through normative-philosophical, juridical, and conceptual approaches. The results of the study show that there is substantive coherence of values between Pancasila and Maqasid Al-Sharia, especially in the orientation towards the protection and maintenance of fundamental aspects of human life (al-kulliyat al-khams), namely hifz al-din (protection of religion), hifz al-nafs (protection of the soul), hifz al-'aql (protection of intellect), hifz al-nasl (protection of descendants), and hifz al-mal (protection of property). These values are implicitly internalized in the precepts of Pancasila which emphasizes the principles of divinity, humanity, unity, deliberative democracy, and social justice. Thus, there is no epistemological or axiological contradiction between the two, but rather a relationship that is complementary and mutually reinforcing. The theoretical implications of this study confirm the importance of developing an integrative paradigm between state ideology and sharia principles within the framework of modern nation-states. Meanwhile, practically, the results of this research contribute to strengthening the ethical basis in public policy formulation, national legal development, and governance oriented to public interest, substantive justice, and respect for Human Rights (HAM). Thus, the harmonization of the values of Pancasila and Maqasid al-Syariah is a strategic foundation in building an inclusive, fair, and sustainable life of the nation and state within the framework of the Republic of Indonesia.